Analisis Yuridis Terhadap Pencurian Hasil Kebun Kelapa Sawit Rakyat Setelah Terbitnya Peraturan mahkamah Agung (Perma) No. 2. Tahun 2012 - Ginting, Sejahtera Immanuel; Isnaini, Isnaini; Zulyadi, Rizkan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
he rise of criminal acts of theft of oil palm plantations is mainly due to law enforcement that is not firm in the sense that it cannot have a deterrent effect on perpetrators of criminal acts. This is because many of the theft cases have a value of less than Rp. 2,500,000, so it is considered a minor crime. This causes people who have lost most of their livelihoods to feel frustrated, causing some people to lose their minds by taking vigilante actions. Based on this, the formulation of the problem in this study: 1) What are the legal rules regarding theft after the issuance of Perma No. 2 of 2012 in Indonesia. 2) How to steal people's oil palm plantations afterithe issuanceiof Perma No. 2 of 2012 in the Legal Area of Hinai Police, Langkat Regency. 3) How to prevent the loss of smallholder oil palm plantations due to theft of plantation produce which is categorized as a minor crime. The research method used is descriptive method, while the data analysis technique uses qualitative. The results of the study show that the legal regulations regarding light theft after the issuance of Perma Number 2 of 2012 in Indonesia are increasingly less strict. This is because the criminal threa in Article 364 of the Criminal Code, which is only 3 months old, means that suspects or defendants of minor crimes cannot be subject to detention, and the examination procedure used is a quick examination procedure. If referring to the provisions in the Criminal Code and Perma No. 2 of 2012 concerning the limits of adjustmen for minor crimes, then the act is categorized as a minor crime However, if the Plantation Law is used, the perpetrator of a crime will be subject to a threat of 4 years in prison. The police as law enforcer basically do not agree with the issuance of Perma No. 2 of 2012. Theft of people's oil palm plantations after the issuance of Perma No.Â 2 of 2012 in the Legal Territory of the Hinai Police, Langkat Regency, has long been a concern considering the losses caused to oil palm farmers. However, the handling of the perpetrators of the theft of people's garden products tends to be done by mediating, namely seeking so that the victims of theft can get proper compensation for the crops stolen by the perpetrators. The ways that can be done to prevent losses to oil palm plantation farmers due to the theft of their plantation products are: excluding the theft of people's plantation products from minor crimes by implementing the Plantation Law, carrying out strict law enforcement against gardeners who have been harmed by ninja, and urging the farming community to supervise their gardens more by collaborating among farming communities to narrow the space for thieves.